Sustainable diets within sustainable food systems. Issue 1 (14th February 2017) - Meybeck, Alexandre; Gitz, Vincent
Abstract : Sustainable diets and sustainable food systems are increasingly explored by diverse scientific disciplines. They are also recognised by the international community and called upon to orient action towards the eradication of hunger and malnutrition and the fulfilment of sustainable development goals. The aim of the present paper is to briefly consider some of the links between these two notions in order to facilitate the operationalisation of the concept of sustainable diet. The concept of sustainable diet was defined in 2010 combining two totally different perspectives: a nutrition perspective, focused on individuals, and a global sustainability perspective, in all its dimensions: environmental, economic and social. The nutrition perspective can be easily related to health outcomes. The global sustainability perspective is more difficult to analyse directly. We propose that it be measured as the contribution of a diet to the sustainability of food systems. Such an approach, covering the three dimensions of sustainability, enables identification of interactions and interrelations between food systems and diets. It provides opportunities to find levers of change towards sustainability. Diets are both the results and the drivers of food systems. The drivers of change for those variously involved, consumers and private individuals, are different, and can be triggered by different dimensions (heath, environment, social and cultural). Combining different dimensions and reasons for change can help facilitate the transition to sustainable diets, recognising the food system's specificities. The adoption of sustainable diets can be facilitated and enabled by food systems, and by appropriate policies and incentives.